Sustaining character education in pesantren: A holistic and culturally embedded learning ecosystem - Muhammad Anas Ma'arif; Muhamad Arif (Jurnal Cakrawala Pendidikan, 2026)
Character education has become increasingly critical amid growing concerns over moral decline among youth in Indonesia and globally. Islamic boarding schools (pesantren) have long served as traditional institutions that cultivate character in a holistic, immersive environment. However, a comprehensive synthesis of how pesantren implement character education remains limited. Therefore, this study employs a Systematic Literature Review (SLR) methodology, drawing on 50 peer-reviewed articles retrieved from Scopus, Web of Science, and Google Scholar (2015–2025). The findings reveal four key character education models in pesantren: role modeling (uswah hasanah), habituation, curriculum and institutional integration, and pesantren culture as a hidden curriculum. Core character values developed include religious commitment, social responsibility, nationalism, discipline, and independence. Key challenges involve inconsistent curriculum integration, dependence on the kyai as a central role model, diversity of student backgrounds, and external pressures from globalization and digitalization. Theoretically, this study extends the Learning Ecosystems framework (Spencer-Keyse et al., 2020) by introducing pesantren culture as a latent regenerative mechanism that proposed the concept of the Pesantren Latent Regenerative Extension of Learning Ecosystems. These findings offer practical guidance for pesantren in sustaining character education without compromising their distinctive identity.